Quem mata e quem morre? Uma análise das representações sociais construídas sobre os sujeitos “vítima” e “criminoso” na rotina produtiva do blog “o câmera” - Lima, Higo da Silva (Universidade Federal Rural do Semi-Árido, 2018)
Society today is immersed into the explosion of the world wide web that, among its many impacts, enabled the pluralization of channels for the dissemination of content produced and consumed simultaneously by citizens (TARGINO 2009). The journalistic practice is certainly an example of that since it has lost its authority domain on the information production and dissemination for other staff which is also network content producers, this is a phenomenon that can be explained by Lèvy's reflection (2010). This phenomenon can be understood in the light of the proliferation of information and communication technologies -ICT's, which impacted directly on the dynamics of media consumption in order to increase access to internet pages dedicated to the newsworthiness of crimes, violence and unlawful conduct. This work aims to launch a closer look at the phenomenon of social representations exposed by Foucault (1987, 1995, 1999, 2005 and 2008) from the postings about violence during the period of a week of virtual content in www.ocamera.com.br in order to identify the construction of subject represented on the journalistic narrative as it is considered "victimized" and "criminals" (MISSE, 2010). Therefore, "violence", "crime" and the "unlawful conduct" are theoretical frameworks based on the studies of Muchemblend (2012), Martucelli (1999), Garland (2008) et al. to understand the phenomenon that intersects with the media. The content review in the light of critical discourse analysis allows us to have the right conclusion about the central role of the media in the scheduling of public debate, especially in face of the proliferation of information and communication technology devices which provide a changing in the narrative construction of journalism in order to reaffirm social stratified representations of the subject
Keywords: Mídia; Comunicação; Jornalismo; Violência; Crime; Representações Sociais; Media; Communication; Journalism; Violence; Crime; Social Representations; MULTIDISCIPLINAR::INTERDISCIPLINAR::COGNIÇÃO, TECNOLOGIAS E INSTITUIÇÕES